PENGEMBANGAN MEDIA APLIKASI PEMBELAJARAN GERBANG LOGIKA DASAR UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH MENENGAH KEJURUAN - Syahputra, Darma; Dewi, Happy Indira (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to develop a learning application media for basic logic gates that is feasible and effective for use in learning in vocational high schools. This study uses the Research and Development (R&D) method with the development of the ADDIE model. The subjects in this study were students and teachers of class X TITL SMK Negeri 1 Aceh Barat Daya. The data analysis technique used is qualitative quantitative analysis. The results of the study indicate that the learning application media is feasible for use based on testing by material experts with a score percentage of 91%